FORMATION OF ECONOMIC CONCEPTION ABOUT GLOBALIZATION: TO PROBLEM OF STATEMENT - Aitov, S. Sh. (Science and Transport Progress, 2004)
The article analyses the issue of peculiarities and stages of development of economic theories about globalization processes.